A case of sub-acute compartment syndrome of bilateral pectoralis major, deltoid and triceps muscles. (October 2022) - Kalaskar, A; Paniker, J; Gavai, P
A 19-year-old healthy bodybuilder presented to the emergency department with gradually worsening pain in both his upper arms and shoulders and inability to fully flex his elbows. The haematological investigations revealed a markedly raised Creatinine Kinase (74, 400 U/L) and myoglobinuria. The patient required an emergency surgical decompression of the pectoral and the anterior and posterior compartments of arms of both upper limbs with secondary closure after 48 h. The patient had an uneventful post-op and recovery of his functions with some initial restriction of full flexion of his left elbow and some weakness in his triceps, all of which gradually improved.